Larval dispersal patterns and connectivity of Acropora on Florida’s Coral Reef and its implications for restoration - Samantha King; Antoine Saint-Amand; Brian K. Walker; Emmanuel Hanert; Emmanuel Hanert; Joana Figueiredo (Frontiers in Marine Science, 2023)
Since the 1980s, populations of Acropora cervicornis and A. palmata have experienced severe declines due to disease and anthropogenic stressors; resulting in their listing as threatened, and their need for restoration. In this study, larval survival and competency data were collected and used to calibrate a very high-resolution hydrodynamic model (up to 100m) to determine the dispersal patterns of Acropora species along the Florida’s Coral Reef. The resulting connectivity matrices was incorporated into a metapopulation model to compare strategies for restoring Acropora populations. This study found that Florida’s Coral Reef was historically a well-connected system, and that spatially selective restoration may be able to stimulate natural recovery. Acropora larvae are predominantly transported northward along the Florida’s Coral Reef, however southward transport also occurs, driven by tides and baroclinic eddies. Local retention and self-recruitment processes were strong for a broadcast spawner with a long pelagic larval duration. Model simulations demonstrate that it is beneficial to spread restoration effort across more reefs, rather than focusing on a few reefs. Differences in population patchiness between the Acropora cervicornis and A. palmata drive the need for different approaches to their management plans. This model can be used as a tool to address the species-specific management to restore genotypically diverse Acropora populations on the Florida’s Coral Reef, and its methods could be expanded to other vulnerable populations.